Practice Model of Read-Examine-Decide-Write Strategy In Strengthening Students’ Reading Comprehension - Mufaridah, Fitrotul (Universitas Muhammadiyah Jember, 2016)
Teaching reading in ESP Class is a challenging work not only for the English teacher but also for the students of Islamic Education Program or PAI of University of Muhammadiyah Jember. Teacher should be selective and creative in implementing teaching strategy in order to encourage students to comprehend reading text and communicate their understanding in the target language. The implementation of Read-Examine-Decide-Write (REDW) Strategy was done in ESP class of PAI. Read-Examine-Decide-Write Strategy was found as a good solution to teach them reading comprehension. By grouping the students in pair, they did their learning effectively through the steps of REDW. 75.8% or 22 of 29 students got score ≥ 75. They were active in comprehending the text through steps of REDW. The research result showed that Read-Examine-Decide-Write Strategy was able to improve PAI students’ reading comprehension in the first semester of 2015-2016 Academic Year.Keywords: reading comprehension, read-examine-decide-write strategy